Dynamic Tracking of Lung Deformation during Breathing by Using Particle Method. (17th July 2009) - Chhatkuli, Subas; Koshizuka, Seiichi; Uesaka, Mitsuru
Abstract : To reduce the side effects and to improve the efficiency of radiation therapy in lung cancer, a pinpoint radiation therapy system is under development. In the system, the movement of lung tumor during breathing could be estimated by employing a suitable numerical modeling technique. This paper presents a gridless numerical technique called Moving Particle Semi-implicit (MPS) method to simulate the lung deformation during breathing. The potential of the proposed method to employ in the future pinpoint radiation therapy system has been explored. Deformation of lung during breathing was dynamically tracked and compared against the experimental results at two different locations (upper lobe and lower lobe). Numerical simulations showed that the deformation of lung surface ranged from less than 4 mm to over 20 mm depending on the location at the surface of lung. The simulation showed that the lower section of lung exhibited comparatively large displacement than the upper section. Comparing with the experimental data, the lung surface displacement during inspiration process was predicted reasonably well. Comparison of numerical prediction with experimental observations showed that the root mean squared error was about 2 mm at lower lobe and less than 1 mm at upper lobe at lung surface.